Bridging the digital divide for individuals with intellectual disabilities: Implications for well-being and inclusion. - Murphy, Esther; Fiori, Sara; Mc Causland, Darren (My University, 2025)
Background: Developments in digital technologies have transformed how people interact with the world, offering employment, education, communication, health benefits and entertainment. Research has shown that not everyone can easily access digital content, particularly people with intellectual disabilities. Despite internet access being recognised as a human right in the United Nations' Conventions on the Rights of Persons with Disabilities, this group faces significant disadvantages. Methods: A thematic analysis of quantitative and qualitative findings was conducted with data from focus groups and interviews with 200+ participants across Ireland, Sweden, France, and the Netherlands on how people with intellectual disabilities are using technology at this time and access facilitators and barriers. Findings: The pandemic exacerbated the digital divide between people with intellectual disabilities and their neurotypical peers, impacting physical and mental well‐being. Growing demand for accessible digital skills training underscores the need to bridge this gap. Conclusion: Addressing these digital access disparities is crucial to ensure that individuals with intellectual disabilities can enjoy the benefits of the digital age and maintain their well‐being. By identifying priority topics in our interview data, researchers also pinpointed critical accessibility barriers and facilitators to support codesigning activities for future digital skills education content within the Digi‐ID project.
PUBLISHED
doi.org/10.1111/bld.12613
Keywords: collaborative practice; empowerment issues; health; inclusive education; intellectual disability; mental health; Digital Engagement; Identities in Transformation; Inclusive Society; Computer Education/Literacy; Digital Inclusion; Disability Inclusion; Education and Work; HUMAN COMPUTER INTERACTION; INTELLECTUAL DISABILITY; Inclusive Education; Inclusive pedagogy for adults with intellectual disabilities; Information technology in education; Innovative Pedagogy; Intellectual Disability; LEARNING DISABILITY; Lifelong Learning; Participatory Research Methods; Public Engagement; Intellectual Disability; Accessibility; Community; Social participation